Tectonic inversion in the Santa Barbara System of the central Andean foreland thrust belt, northwestern Argentina - Kley, Jonas (2002)
The Santa Barbara System (SBS) of northern Argentina is a 400 km long segment of the Subandean foreland thrust belt. It is characterized by predominantly west verging, relatively high-angle thrust faults. Many of these faults are reactivated normal faults from one branch of a complex Cretaceous to Paleogene rift system. Heteroaxial folding in parts of the SBS is probably due to a slight component of range-parallel dextral strike-slip motion acting on preexisting faults striking north and NE during inversion. Regional balanced cross sections along two transects across the northern SBS indicate that the major faults flatten into a detachment in the basement at about 10 km depth. Neogene E-W contraction in the SBS is of the order of 21-26 km. Rift extension is not very well constrained but was probably less than 10 km. The structural style of the SBS differs from the thin-skinned Subandean thrust belt to the north and from the large-wavelength Sierras Pampeanas basement uplifts to the south. The changes between the different styles are sharp and coincide with the northern and southern boundaries of the rift in the foreland, suggesting that crustal or lithospheric heterogeneities exert an overriding control on foreland structural style.